Monitoring a Mandatory Nonmedical Switching Policy from Originator to Biosimilar Infliximab in Patients with Inflammatory Bowel Diseases: A Population-Based Cohort Study. (1st March 2023) - Fisher, Anat; Kim, Jason D.; Dormuth, Colin R.
Abstract : Background . On September 5, 2019, British Columbia announced a new policy (the Biosimilars Initiative) to switch from originator to biosimilar infliximab for patients with inflammatory bowel diseases. Objective . To monitor the impacts of the policy on the use of medications and health services during the first year of the policy. Methods . In this population-based cohort study, we used administrative health data to construct three historical cohorts and one policy cohort of patients with inflammatory bowel diseases who used the originator infliximab. We then monitored the cumulative incidence of medications and health services. Log-likelihood ratios were used to quantify differences between the policy cohort and the average of the historical cohorts. Results . The cohorts included 1839–2368 users of the originator infliximab, ages 4–90 years, mean age 43 years. During the first year of follow-up, we found: (1) a 0.9% increase in the first dispensation of infliximab, biosimilar, or originator; (2) a 16.2% increase in infliximab dose escalation; (3) a decrease of 2.4% in the dispensation of antibiotics and a 2.6% decrease in new use of prednison; (4) an anticipated increase in visits to physicians and gastroenterologists to manage switching to biosimilars (24.0%); (5) a 4.0% decrease in discharges from hospital; and (6) a 2.9% decrease in emergency admissions to hospital. Conclusion . British Columbia's Biosimilars Initiative for nonmedical switching from originator to biosimilar infliximab for inflammatory bowel diseases was not associated with harmful impacts on medications and health services use. An increase in dose escalation was accompanied by an improvement in health status proxies.